Risk analysis for patients with a functionally univentricular heart after systemic-to-pulmonary shunt placement. (13th March 2021) - Ide, Yujiro; Tachimori, Hisateru; Hirata, Yasutaka; Hirahara, Norimichi; Ota, Noritaka; Sakamoto, Kisaburo; Ikeda, Tadashi; Minatoya, Kenji
Abstract:  : OBJECTIVES: To investigate risk factors for mortality after systemic-to-pulmonary (SP) shunt procedures in patients with a functionally univentricular heart using the Japan Cardiovascular Surgery Database registry. METHODS: Clinical data from 75 domestic institutions were collected. Overall, 812 patients with a functionally univentricular heart who underwent initial SP shunt palliation were eligible for analysis. Patients with pulmonary atresia with an intact ventricular septum and patients with a SP shunt as part of the Norwood procedure were excluded. Risk factors for 30- and 90-day mortalities were analysed using a logistic regression model. RESULTS: Median age and body weight at SP shunt placement were 41 days and 3.6 kg, respectively. Modified Blalock–Taussig shunt, central shunt and other types of SP shunts were applied in 689 (84.9%), 94 (11.8%) and 30 (3.7%) patients, respectively. Cardiopulmonary bypass was utilized in 410 patients (51%) for 128 min (median, 19–561). There were 411 isolated SP shunt procedures. Median hospital stay was 27 days, and 742 (91.4%) patients were discharged. The 30- and 90-day mortality rates were 3.4% and 6.0%, respectively. Placement of a central shunt was identified as a risk factor for 30-day mortality, while lower body weight, preoperative ventilator support, right atrial isomerism and coexistence of major aortopulmonary collateral arteries and an unbalanced atrioventricular septal defect were identified as risk factors for 90-day mortality. CONCLUSIONS: SP shunt carries a high mortality rate in patients with a functionally univentricular heart when it is performed in smaller patients with complex cardiac anomalies.